MEMBANGUN KONSEP DAN JIWA WIRAUSAHA BAGI MAHASISWA PADA PERGURUAN TINGGI - Luh Kompiang Sari (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2019)
The era of globalization requires excellence, equity, resilience and competition will change the educational paradigm. Efforts to build the quality and quantity of human resource development in entrepreneurship, the business in the field of formal education both at the school and college level has the potential, to build enthusiasm and develop entrepreneurial spirit in students. Entrepreneurship is an ability (ability) in creative thinking and innovative behavior that is made the basis as a resource, driving force, tactics, tips and processes in facing life’s challenges. Thus entrepreneurship is very important to instill and teach as an independent scientific discipline in the preparation and use of skilled and professional human resources. Keywords ; Concept, Value of Entrepreneurship